Hubungan antara Optimisme Karier dengan Adaptabilitas Karier pada Mahasiswa - Risma Diana Hartati Sinaga; William Gunawan (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
The rapid advancement of technology has brought significant changes in various aspects of life, including the world of work. Therefore, students who want to build a successful career must proactively develop their abilities. This study focuses on analyzing the correlation between career optimism and students' career adaptability by involving 40 higher education institutions in the DKI Jakarta area. The hypothesis in this study shows that there is a significant positive relationship between career optimism and career adaptability in university students in DKI Jakarta. This study involved 428 active students aged 18-25 years as research subjects so that the sampling technique used was purposive sampling. Quantitative approach with Career Optimism scale (α = 0.85) and Career Adapt-Ability Scale Short Form (α = 0.849). The data that has been obtained is analyzed using the Spearman Correlation technique. The results of this study showed a significant positive correlation (r = 0.223, p < 0.05). This shows that the higher the level of career optimism, the higher the career adaptability of college students in DKI Jakarta. This study can be implied to prepare students from the world of education to the world of careers.